Promoting students’ metacognitive awareness and cognitive learning outcomes in science education - Silfia Ilma; Mimien Henie Irawati Al Muhdhar; Fatchur Rohman; Murni Sapta Sari (Institute of Advanced Engineering and Science, 2022)
This research aimed to investigate the effect of project-based learning (PjBL), predict-observe-explain (POE), and predict-observe-explain based project (POEP) on metacognitive awareness and cognitive learning outcomes in biology learning. The research used a pretest-posttest non-equivalent control group design. The experiment was conducted from August to December 2020. The metacognitive awareness questionnaire was applied to measure students’ metacognitive awareness. Besides, an essay test was used to assess cognitive learning outcomes. Data collection in this study was carried out using Google Form, Google Classroom, Google Meet, and WhatsApp. Data analysis using statistical product and service solutions (SPSS) version 23 software. The analysis of covariance (ANCOVA) results analysis showed that PjBL, POE, and POEP affected students’ metacognitive awareness and cognitive learning outcomes in biology learning with a value of p<0.005. The least significant different (LSD) result was significantly different in improving students’ metacognitive awareness and cognitive learning outcomes. The POEP class gained the highest posttest score. Therefore, POEP could be applicable to improve students’ metacognitive awareness and cognitive learning outcomes in Biology learning.